Marker development for quality protein maize breeding and an interaction study between Opaque-2 and Ask2 genes - Hernández Rodríguez, Martha; Babu, Raman; Skinner, Debra J.; Palacios Rojas, Natalia; Martins, Marina C.M.; García Zavala, J. Jesús; Lobato Ortiz, Ricardo; Santacruz Varela, Amalio; Castillo-González, Fernando; Yunbi Xu; Boddupalli, P.M. (Sociedad Mexicana de Fitogenetica A.C, 2022)
Quality Protein Maize (QPM) kernels contain twice the amounts of lysine and tryptophan compared to normal corn kernels. Although the opaque-2 (o2) mutation is the underlying cause of this beneficial change, other genes such as Aspartate kinase-2 (Ask2) affect the amino acid content in the endosperm to a lesser degree. To date, reports on the interaction between both loci are scarce and there are no high-throughput assays for the identification of the alleles of these genes. The objectives of this research were: 1) to study the interaction between the o2 and Ask2 genes with respect to the accumulation of amino acids in the endosperm in an F2 population, 2) to identify conserved SNPs into the o2 gene that can be used as markers, 3) to estimate the frequency of an SNP of Ask2 associated with the accumulation of lysine in the endosperm in CIMMYT germplasm, and 4) to develop high-throughput marker assays for these SNPs. The interaction study showed a preponderant effect of o2 on the accumulation of 11 amino acids (P ≤ 0.01). Ask2 appeared only to act with o2 to enhance marginally lysine, histidine and methionine levels in the double recessive homozygotes. Sequencing of amplicons at the o2 locus led to the identification of an SNP in exon 1 that discriminated all QPM (C) genotypes from non-QPM (T) genotypes. Validation of this SNP through KASP™ assays indicated that it was 92 % assertive in differentiating the o2 genotypes. In contrast, the frequency of the Ask2 SNP in CIMMYT QPM germplasm was low; however, an SSCP marker developed using this SNP detected five variants indicating that other unknown base changes may confer positive lysine-increasing responses. These markers could aid the marker-assisted selection of QPM cultivars.